2015
DOI: 10.21608/ejar.2015.152458
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Histological Effects of Metarhiziumanisopliae on the Cotton Leafworm, Spodoptera Littoralis (Boisd.) (Lepidoptera: Noctuidae)

Abstract: oxicological, biological and histological effects of the isolated entomopathogenic fungus Metarhizium anisopliae from the red palm weevil adult on the newly molted 2 nd and 4 th instar larvae of the Egyptian cotton leaf worm, Spodoptera littoralis (Boisd.), were investigated under laboratory conditions at 27º ± 2º and 60% ± 5% R.H. Results revealed a decrease in the mean larval, pupal, and adult durations for the 2 nd and 4 th instar larvae surviving treatment with the LC 50 of 2.8x10 8 and 2.8x10 9 spore/ml f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…While in figures (3 & 4) we found that within the midgut lumen, there is a thin membrane surrounding food mass, a musculosa surrounds the epithelial layer, composed an inner and out layer of longitudinal muscle. His with agree Lofty, Dalia et al, (2016) which reported that midgut containing different cell (i) A majority of columnar cells, (ii) Goblet cells are seen between columnar cells. (iii) Regenerative cells are small in size and are round or elongated.…”
Section: Table 3: Comparison Between the Two Artificial Diets And Nor...mentioning
confidence: 68%
“…While in figures (3 & 4) we found that within the midgut lumen, there is a thin membrane surrounding food mass, a musculosa surrounds the epithelial layer, composed an inner and out layer of longitudinal muscle. His with agree Lofty, Dalia et al, (2016) which reported that midgut containing different cell (i) A majority of columnar cells, (ii) Goblet cells are seen between columnar cells. (iii) Regenerative cells are small in size and are round or elongated.…”
Section: Table 3: Comparison Between the Two Artificial Diets And Nor...mentioning
confidence: 68%